The Panentheism of Karl Christian Friedrich Krause (1781-1832) From Transcendental Philosophy to Metaphysics - Göcke, Benedikt Paul (Berliner Bibliothek, 2018)
The book provides the first analysis of Karl Christian Friedrich Krause's system of philosophy and his panentheism in English. Karl Christian Friedrich Krause has bequeathed to us a system of philosophy which is little recognised in contemporary philosophy. This is both surprising and unfortunate, because Krause's philosophical system has much to offer: Through transcendental reflection on the nature of the human, Krause understands God as the one infinite and unconditioned reality, and the ultimate necessary condition of knowledge. God makes humanity, nature, and reason ultimately comprehensible as the essential categories of the divine Essence. God is thus the single, primary, object of science that is already logically presupposed even before His discovery. Science presupposes theology, and theology is best read as panentheism.